1999
DOI: 10.1073/pnas.96.23.13300
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of premutagenic DNA lesions in mice defective in removal of oxidative base damage

Abstract: DNA damage generated by oxidant byproducts of cellular metabolism has been proposed as a key factor in cancer and aging. Oxygen free radicals cause predominantly base damage in DNA, and the most frequent mutagenic base lesion is 7,8-dihydro-8-oxoguanine (8-oxoG). This altered base can pair with A as well as C residues, leading to a greatly increased frequency of spontaneous G.C-->T.A transversion mutations in repair-deficient bacterial and yeast cells. Eukaryotic cells use a specific DNA glycosylase, the produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
541
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 740 publications
(567 citation statements)
references
References 43 publications
24
541
0
2
Order By: Relevance
“…The four DNA glycosylases each function in the suppression of mutations by 8-oxo-Gua in DNA. The overlapped recognition of 8-oxo-Gua could explain the fact that single knock-out mice deficient in OGG1, MUTYH, NTH1, and NEIL1 show few tumor phenotypes [57,[65][66][67][68][69][70][71]. In contrast, there is evidence to support the view that polymorphisms in these DNA glycosylases are associated with human carcinogenesis (reviewed in 72).…”
Section: Discussionmentioning
confidence: 99%
“…The four DNA glycosylases each function in the suppression of mutations by 8-oxo-Gua in DNA. The overlapped recognition of 8-oxo-Gua could explain the fact that single knock-out mice deficient in OGG1, MUTYH, NTH1, and NEIL1 show few tumor phenotypes [57,[65][66][67][68][69][70][71]. In contrast, there is evidence to support the view that polymorphisms in these DNA glycosylases are associated with human carcinogenesis (reviewed in 72).…”
Section: Discussionmentioning
confidence: 99%
“…While Ogg1 2/2 mice have been shown to accumulate 8-oxoG in liver [Klungland et al, 1999;Osterod et al, 2001], most studies have not demonstrated them to be prone to spontaneous tumor formation relative to WT controls [Klungland et al, 1999]. Similarly, a novel model of OGG1 deficiency also reported a significant increase in 8-oxoG lesions, associated with increased mutagenesis of a transgenic gpt gene [Minowa et al, 2000;Arai et al, 2002Arai et al, , 2003].…”
Section: Actions Of Ber Glycosylases In Disease States Obesity and Mementioning
confidence: 99%
“…Despite the progress in characterizing ROS effects on lipids (resulting in peroxidation), proteins (resulting in SH-group oxidation and formation of carbonyls), and DNA (formation of 8-OH guanosine and of single and double strand breaks) (29,30), the particular impact of potential sites relevant for cellular superoxide and hydrogen peroxide generation in brain tissue is less clear. Within the respiratory chain complex I, the FMN moiety (31,32), iron-sulfur clusters (33,34), and semiquinones (35) have been suggested to be responsible for mitochondrial superoxide production.…”
Section: Mitochondrial Formation Of Ros and Neurodegenerationmentioning
confidence: 99%